1987
DOI: 10.1177/000331978703800802
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheology in Surgery—A Review

Abstract: The rheological behavior of blood and its components under physiologic and pathophysiologic conditions is reviewed, with a focus on the type and extent of pathohemorheological changes in surgical patients during hospitalization and thereafter, as well as their clinical consequences with regard to thromboembolic complications. During the operation and the postoperative period various hemorheological and hemostasiological alterations acquire clinical significance: 1. hyperreagibility of platelets with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Besides, metabolic changes and tissue perfusion due to cardiovascular problems may lead to inadequate recovery in plasma viscosity (41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, metabolic changes and tissue perfusion due to cardiovascular problems may lead to inadequate recovery in plasma viscosity (41).…”
Section: Resultsmentioning
confidence: 99%
“…However, whether these agents change plasma rheology and/or anesthesia may result in deterioration of tissue perfusion remains controversial. Changes in plasma viscosity have been listed among the factors associated with anesthesia procedures responsible for deterioration of tissue and organ perfusion (16,17). After surgical procedures performed using general anesthesia, erythrocyte deformability and increased aggregation may be observed (17).…”
mentioning
confidence: 99%
“…Additionally, it has been suggested that the impaired perfusion at the tissue level observed as a complication of diabetes mellitus is primarily due to the reduced erythrocyte deformability (33,34). Besides, metabolic changes and tissue perfusion due to cardiovascular problems may lead to an inadequate recovery in plasma viscosity (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether these agents change plasma rheology and/or anesthesia may result in deterioration of tissue perfusion remains controversial. Changes in plasma viscosity have been listed among the factors associated with anesthesia procedures responsible for deterioration of tissue and organ perfusion (2,3). Erythrocyte deformability and increased aggregation may be observed after surgical procedures performed under general anesthesia (3).…”
mentioning
confidence: 99%
“…Disorders in the hemorheologic state may lead to an inadequate recovery in plasma viscosity (2). Erythrocyte deformability and plasma viscosity are important factors that affect organ and tissue perfusion (4).…”
mentioning
confidence: 99%